تقييم سريري لكفاءة الكومبومير السني على الأسنان الخلفية - خليل, رأفت; معروف, علي (Latakia University Journal -Medical Sciences Series, 2019)
يهدف البحث إلى تقييم الكفاءة السريرية لمادتين من الكومبومير السني المستخدمة على السطح الطاحن للأسنان الخلفية الدائمة بعد مرور عام و ثلاثة أعوام . ولقد تم اعتماد معيار ( USPHS ) المعدل في تقييم نتائج المادتين وهما (Compoglass F وDyract Ap ) إذ تم اعتماد المعايير المناسبة لكل من التوافق اللوني للحشوات مع نسج السن والانطباق الحفافي والتبدل اللوني ووجود أم عدم وجود نخور ثانوية حول حشوات الكومبومير السني المرممة على الأسنان الخلفية للمرضى . النتائج: حللت النتائج باستخدام(One Way ANOVA) و (Tukey's test ) وكذلك (Kruskal-Wallis test) بنسبة خطأ ( 0.05 ≥P ) للتحقق من القيم المتجانسة, وكان البرنامج المستخدم هو (SPSS Inc. Chicago, IL,USA Sigma Stat 3.01,) و بعد مرور سنة و ثلاث سنوات تبين أنه يوجد اختلاف جوهري على المستوى(B) في التوافق اللوني و التبدل اللوني الحفافي بين سنة و ثلاث سنوات على المستوى (B) بالنسبة للمادتين موضوع الدراسة, في حين أنه لم يكن هناك أي نوع من النخور الثانوية حول كل الحشوات المطبقة. واعتبرت مادة الـ Dyr- p أفضل من مادة الـ Comp.F بالنسبة لخاصية الانطباق الحفافي على المستوى(B) وذلك بعد مرور ثلاث سنوات. This research was conducted to assess the clinical performance of two dental compomer materials (Dyract Ap and Compoglass F), which are used on the occlusal surface of posterior teeth. The restorations were clinically evaluated at baseline and at one and three years intervals using the modified (USPHS) criteria for colour mismatch, marginal discoloration, marginal adaptation, and secondary caries was used to assess the results. Data was submitted to the Friedman's Test, ANOVA with repetitive measures, and Tuky,s Tests, all at a significance level of p≤0.05. When comparing the materials, Compoglass F (R) and Dyract Ap presented similar clinical performance after one and two years. The results showed that there are significant differences at the level (B) between the two materials relating colour mismatch; and, marginal discoloration after one and three years. But there were no significant differences relating secondary caries. The results showed that Dyr-p better than Comp-F relating to marginal adaptation at the level (B) after three years.